Unlocking the Potential of Cimetidine: Enhancing FOXP3+Treg Cells and pRB Expression in Condyloma Acuminatum Treatment - Prasetyadi Mawardi; Lian Kamilah; Pratiwi Prasetya Pramisawitri; Bobby Febrianto; Endra Yustin Ellistasari; Ayu Kusuma Dewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Condyloma acuminatum (CA), caused predominantly by Human Papilloma Virus (HPV) types 6 and 11, remains a frequent sexually transmitted infection with malignant potential. Immune dysregulation and viral oncogenic proteins contribute to this risk. Cimetidine, an H2-receptor antagonist with immunomodulatory properties, has been proposed as an adjunctive therapy. Purpose: To evaluate the efficacy of oral cimetidine supplementation on FOXP3+ Treg cells and pRB expression in CA. Methods: An experimental pre-post test study was conducted in CA patients attending the Dermatovenereology Outpatient Clinic of Dr. Moewardi General Hospital, Surakarta, Indonesia, from October 2022 to March 2023. Subjects were allocated into two groups: one received oral cimetidine 400 mg for three months, while the control group did not. Both groups received standard therapy, including chemical cautery and cryotherapy, for four weeks. Immunohistochemical staining was performed on skin biopsy specimens before and after treatment to evaluate FOXP3+ Treg cells and pRB expression at the Department of Anatomical Pathology, Faculty of Medicine, Sebelas Maret University, Surakarta, Indonesia. Data were statistically analyzed, and p<0.05 was considered significant. Result: Thirty-six patients with CA were included in this study, comprising 20 subjects who received oral cimetidine and 16 subjects as controls. The subjects were predominantly male (68.75%). The Mann-Whitney test showed a significant difference of pRB expression between both groups (p=0.004), while the FOXP3+ Treg cell analysis was not statistically significant (p=0.072). Conclusion: Oral cimetidine supplementation increases pRB expression and may help prevent the development of CA but not FOXP3+ Treg cell expression